2018
DOI: 10.12890/2018_000900
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Primary Retroperitoneal Germ Cell Tumour in a Young Man

Abstract: Some 2–5% of germ cell tumours are of extragonadal origin, with a retroperitoneal location being very rare. The majority of retroperitoneal germ cell tumours have metastasized from a testicular tumour. These tumours are diagnosed incidentally or symptomatically and nearly all present with high alpha-fetoprotein and lactate dehydrogenase levels.We describe the unusual case of a 31-year-old man with a yolk-sac, retroperitoneal germ cell tumour, with normal serum alpha-fetoprotein and lactate dehydrogenase levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, there are some studies on the abnormal expression of LDH in tumors, and many scholars take it as one of the prognostic indicators [ 15 , 16 ]. Existing studies have demonstrated that elevated LDH in tumor tissue is associated with the clinical outcomes of multiple cancers, including renal cell carcinoma, melanoma, prostate cancer, lung cancer, and colorectal cancer [ 17 , 18 ]. Could α-HBDH also be a biomarker for the prognosis and diagnosis of lung cancer?…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some studies on the abnormal expression of LDH in tumors, and many scholars take it as one of the prognostic indicators [ 15 , 16 ]. Existing studies have demonstrated that elevated LDH in tumor tissue is associated with the clinical outcomes of multiple cancers, including renal cell carcinoma, melanoma, prostate cancer, lung cancer, and colorectal cancer [ 17 , 18 ]. Could α-HBDH also be a biomarker for the prognosis and diagnosis of lung cancer?…”
Section: Introductionmentioning
confidence: 99%